Evaluation of Early Intervention Impact in Alentejo- Child, family and community - Franco, Vitor (2009)
Reseach about the impact of the Early Intervention System en Alentejo, Portugal. The investigation project “Evaluation of early intervention impact in Alentejo” was the consequence of several actions that, in the past 7 years, provided the three districts of Alentejo with an early intervention child development net, that was pioneered in Portugal and that brings together the initiatives from the regional services of the Health, Education and Social Security Ministries along with private non-profitable institutions of social care. For the first time, it was possible to create a large, uniform net, covering a large area, with a coordinated structure and articulated work and intervention models, laying down as the main purpose support to children with developmental disturbances or in risk, and the families of those children.